Evidence for asialo GM1 as a corneal glycolipid receptor for Pseudomonas aeruginosa adhesion. - Hazlett, L D (1993)
Anti-gangliotetraosylceramide (anti-asialo GM1) and antiparagloboside monoclonal antibodies (MAbs) were used in immunofluorescence, immunoelectron-microscopic, and in vitro binding inhibition assays to determine whether either of the glycolipids was detectable in the normal cornea, whether levels changed following corneal scarification and either trypsin treatment or incubation in vitro with Pseudomonas aeruginosa, and whether either of the MAbs could competitively inhibit P. aeruginosa binding to cornea. No immunostaining above background for either glycolipid was observed in frozen, unfixed sections or in lightly fixed, K4M-embedded antibody-gold-labeled thin sections of normal cornea. In frozen sections of organ-cultured scarified cornea, no increased immunostaining for anti-asialo GM1 or antiparagloboside reactivity was noted immediately or 60 min after corneal scarification. However, at 60 min after scarification and in vitro incubation of the eye with either trypsin or P. aeruginosa, enhanced immunostaining for both glycolipids was associated with cells within or immediately adjacent to the wound site. Trypsin increased immunoreactivity in the wound site more markedly compared with incubation with P. aeruginosa, but immunostaining was similarly localized with either treatment. No staining above background was seen in control sections. Similarly, with immunoelectron microscopy, increased immunogold-MAb staining for both glycolipids was seen on the plasma membranes of the wound-site cells of eyes incubated with either trypsin or P. aeruginosa compared with controls that were similarly immunostained but with the primary antibody either omitted or substituted with a nonspecific MAb. Competitive binding inhibition assays, in which the bacterial inoculum or the eye in organ culture was incubated with anti-asialo GM1 MAb prior to topical ocular application of the bacteria, showed significantly decreased P. aeruginosa adhesion compared with preparations similarly treated with phosphate-buffered saline or antiparagloboside MAb. These data provide evidence to support the hypothesis that asialo GM1, not paragloboside, serves as a receptor for P. aeruginosa binding to the scarified cornea of the adult mouse and spatially localizes both glycolipids in the wound site.